Hagiastridae Species from Karimia Formation (Upper Jurassic-Lower Cretaceous) Northren Iraq - Al-Dulaimi, Salam (Iraqi Journal of Science, 2025)
The Hagiastridae Reidel include Spongodiscacea with two, three or four rayed test comprised of layered spongy meshwork lacking concentric ring or spirl. This family appears to be restricted to the Mesozoic (1, 2, 3). It has ageologic history extending at least as far as the Jurassic. The majority of Hagiastridae species are distinctive and with short range.Seven species of Hagiastridae: Paronaella ewingi, Halesium quadratum, Patulibracchium inaequalum, Patulibracchium marshensis, Hagiastrum plenum, Crucella messinae, Crucella irwini, have been described. They are frome the upper Jurassic-lower Cretaceous Karimia Formation of northren Iraq.